Rapid profiling of triglycerides in human breast milk using liquid extraction surface analysis Fourier transform mass spectrometry reveals new very long chain fatty acids and differences within individuals. (16th July 2019) - Koulman, Albert; Furse, Samuel; Baumert, Mark; Goldberg, Gail; Bluck, Les
Abstract : Rationale: We describe a novel method for preparing milk samples and profiling their triglyceride (TG) fractions. This method was used to explore how the TG profile of milk modulates as lactation progresses and how the TG profile differs between breasts. Methods: Fresh milk was spotted onto Whatman filter paper and air‐dried. Liquid Extraction Surface Analysis coupled to Fourier Transform Mass Spectrometry (LESA‐MS) was adapted for molecular profiling. Collision‐Induced Dissociation (CID) was used to profile fatty acid residues. Results: LESA‐MS produced the relative abundances of all isobaric TGs described and showed that mammary glands within one individual can produce a different profile of TGs. CID was used to uncover the configuration of isobaric triglycerides, indicating the relative amounts of the fatty acids contributing to that triglyceride's mass. This also indicated the presence of very long chain fatty acids (C26:0 and C26:1) that have not been reported before in human breast milk. Conclusions: We conclude that spotting on paper and the use of LESA‐MS and CID on milk spots is not only a means for analysing milk in unprecedented detail for this preparation time, but is also amenable to conditions in which collecting and storing fresh milk samples for detailed profiling is prohibitively difficult.